Percutaneous Ultrasound Guided Drainage of Prostatic Abscess in a Dog - Udehiya, Rahul Kumar; Mathew, Dayamon David; Kumar, Vinod; Singh, Naresh Kumar (Biology, Engineering, Medicine and Science Reports)
A 7 year old male German shepherd dog presented with a history of blood in urine at hourly intervals having difficulty in defecation as well. Moreover, it was also loosing body weight during the past few months. Upon, ultrasonography it was observed as prostatic enlargement and diagnosed as prostatic abscess. Subsequently, the treatment went along was with gentamicin irrigation of the abscess after percutaneous drainage under ultrasound guidance and with systemic antimicrobial therapy. Excellent recovery was observed with no further complications seen or reported up to six months following the treatment.
Keywords: Abscess; Ultrasound; Prostate; Gentamycin; Dog